A few-layered Ti3C2 nanosheet/glass fiber composite separator as a lithium polysulphide reservoir for high-performance lithium–sulfur batteries. Issue 16 (6th April 2016) - Lin, Chong; Zhang, Weikun; Wang, Lei; Wang, Zhenggong; Zhao, Wen; Duan, Wenhui; Zhao, Zhigang; Liu, Bin; Jin, Jian
Abstract : A few-layered Ti3 C2 nanosheet/glass fiber composite separator was designed and fabricated as a lithium polysulphide reservoir for high-performance lithium–sulfur batteries. Abstract : We report in this work a new type composite separator that contains a conductive few-layered Ti3 C2 nanosheet and a glass fiber (GF) membrane for lithium–sulfur (Li–S) batteries. Using commercial bulk S (particle size 2–10 μm) as the cathode directly, the Li–S battery delivers an initial discharge capacity of 820 mA h g −1 at a current density of 0.5 A g −1 and a discharge capacity of 721 mA h g −1 after 100 cycles.